Актуальність проблеми майбутніх лідерів глобалізованого світу - Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Біда Олена; Bida Olena; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2025)
Резюме. У статті обґрунтовано перелік лідерських якостей. До переліку таких якостей входить: спроможність управляти собою, повною мірою використовувати свій час, енергію, вміння долати труднощі, виходити зі стресових ситуацій і т. і.; наявність чітких цілей, розуміння реальності поставлених цілей та оцінка просування до них; вміння вирішувати проблеми, виокремлювати головне та другорядне, оцінювати варіанти, прогнозувати наслідки, оцінювати і розподіляти ресурси; творчий підхід до вирішення управлінських задач, вміння генерувати ідеї, готовність до нововведень; знання особливостей організаторської та організаційної діяльності, вміння управляти людьми, мотивувати і стимулювати їх до роботи, вміння працювати з групою, наявність специфічних організаторських якостей особистості.

Abstract. The concept of leadership is understood as the process of managing and organizing a team. In the psychological and pedagogical literature, leadership is called «a typical system of methods of influencing subordinates for a leader (manager)»; «a socio-psychological phenomenon that belongs to dynamic processes in a small group». Defining leadership as a process by which one person influences group members, the main difference between management and leadership is highlighted: these phenomena operate in different structures (management – in a formal structure, and leadership – in an informal structure). One of the most important functions of leaders is compensatory, which is manifested in the elimination of shortcomings in the activities of official leaders. An essential function is also the personification of functional-role relationships, when the leader acts as a kind of emotional center for other people. The qualities inherent in successful leaders are determined. The main variants of leadership styles are distinguished: authoritarian, permissive, balanced, democratic, command, etc. The list of leadership qualities is substantiated. The list of such qualities includes: the ability to manage oneself, to fully use one’s time, energy, the ability to overcome difficulties, to get out of stressful situations, etc.; the presence of clear goals, understanding the reality of the goals set and assessing progress towards them; the ability to solve problems, to distinguish the main and secondary, to evaluate options, predict consequences, evaluate and allocate resources; a creative approach to solving management problems, the ability to generate ideas, readiness for innovations; knowledge of the features of organizational and organizational activities, the ability to manage people, motivate and stimulate them to work, the ability to work with a group, the presence of specific organizational qualities of the individual. Leadership qualities are divided into groups: general managerial (professional competence, practical thinking, sociability, collectivism, organizational skills, hard work, willpower, healthy lifestyle, resilience in stressful situations); leadership qualities (charisma, creativity, courage in generating ideas, initiative, empathy, morality); specific – characteristic of a certain industry.
Relevance of the problem of future leaders of the globalized world
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-14
Keywords: лідерство; функцій лідерів; лідерські якості; процес управління та організації колективом; лідерські стилі